1992
DOI: 10.1002/em.2850200103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on baseline SCE

Abstract: Previous population-based studies have identified subject characteristics that, when combined, can account for approximately 20% of the observed interindividual variation in baseline SCE rates. In the present investigation, a classic twin study design was used to address the issue of the relevance of genetic factors to baseline SCE rates and to identify other demographic, hematologic, and exposure variables predictive of SCE rate. Questionnaire data and peripheral blood samples from 136 monozygotic and 88 dizy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 39 publications
1
9
0
3
Order By: Relevance
“…Age and smoking have been reported to account for about 30% of the variance in SCE frequency (Sarto et al 1985;Hirsch et al 1992). In this study, age and smoking accounted for about 10% of the variation, while VCM exposure contributed 20%.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Age and smoking have been reported to account for about 30% of the variance in SCE frequency (Sarto et al 1985;Hirsch et al 1992). In this study, age and smoking accounted for about 10% of the variation, while VCM exposure contributed 20%.…”
Section: Discussionmentioning
confidence: 49%
“…Interestingly, genotypes explained about 10% of the variation in SCE. A previous study also showed that genetic factors accounted for about 30% of the variation in SCE frequency (Hirsch et al 1992). It will be intriguing to further investigate whether other genotypes contribute to the unexplained variation in SCE frequency.…”
Section: Discussionmentioning
confidence: 87%
“…Consequently, heritable differences in enzymes involved in oxidative metabolism and detoxifying systems can modify levels of induced DNA damage. 17 Individual cancer patients in our study showed different sensitivities and variations in clinical responses even to an identical scheme of chemotherapy, and we assume that it was strongly influenced by their personal genetic background and individual genome sensitivity. It was observed earlier that a small variation in the administered dose of anticancer drugs could lead to severe and life-threatening toxicity in some individuals and poor antitumor effects in others.…”
Section: Discussionmentioning
confidence: 75%
“…Drugi pak navode da HFC mogu biti subpopulacija dugoživućih limfocita u kojima se u uvjetima in vivo, tijekom G 0 -faze, nakuplja više oštećenja, pa prema tome imaju predispoziciju za veći broj SCE. Smatra se da visoke vrijednosti SCE utvrđene u ovim stanicama mogu odražavati kumulativno oštećenje genoma uzrokovano kroničnim izlaganjem mutagenima (125).…”
Section: Izmjene Sestrinskih Kromatida (Sce)unclassified
“…U nekim je istraživanjima dokazan porast učestalosti SCE s dobi (126,127). Žene općenito imaju nešto više vrijednosti SCE od muškaraca (125,127,128,129). Primijećeno je da učestalost SCE raste i tijekom trudnoće, što se pripisuje učinku hormona (130).…”
Section: Izmjene Sestrinskih Kromatida (Sce)unclassified